Experimental Evidence for Stable Ethane Dication in the Gas Phase - D. Stahl; F. Maquin (CHIMIA)
The first experimental proof of the existence of stable ethane dication is reported. This C2H62+ species was generated by charge-stripping reaction in a mass spectrometer.